The influence of self-efficacy, parents' social support and achievement motivation on academic procrastination on students - Werli Erika Sitompul; Ella Silvana Ginting; Suci Pertiwi (Institute of Accounting Research and Novation (IARN), 2022)
This study aims to determine the effect of self-efficacy, parental social support and achievement motivation on academic procrastination in students of the Management Study Program, Faculty of Business, University of Mikroskil Medan. The type of research used is quantitative research. The sampling technique used a probability sampling technique with the proportional stratified random sampling method with a total sample of 211 respondents. The data analysis method used is multiple linear regression. Partial test results (t test) show that partially the variables of Self-Efficacy and Social Support of Parents have a negative and significant effect on Academic Procrastination. While the variable of Achievement Motivation has a positive and significant effect on Academic Procrastination. Simultaneous test results (Test F) show that simultaneously the variables of Self-Efficacy, Parental Social Support and Achievement Motivation have a significant effect on Academic Procrastination with a coefficient of determination (Adjusted R Square) of 0.176 This means that the influence of independent variables, namely self-efficacy, parental social support and achievement motivation on academic procrastination is 17.6 %. While the remaining 82.4 % is influenced by other variables such as self-control, perfectionism, time management, economic difficulties and other variables not exa.